Hukum ekonomi syariah: Pengimplementasian serta penerapannya dalam instansi keuangan di Indonesia - Faradila, Dinda Silvy (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the implementation of Islamic religious teachings in sharia economic law both from the aspect of suitability of the practice of Islamic law in sharia economics in Indonesia. The samples taken were based on a review of the objects needed, such as several banks that implement the sharia system as well as some information about users of the sharia bank access. To get an accurate sample, data was taken from the coordinating ministry for the economy, the coordinating ministry for finance, and so on,as well as Islamic laws which are used as objects of discussion are taken from references such as the Yellow Book, specifically the Muamalah chapter and so on. So that when two discussion samples have been agreed upon, laws can be adopted that are in accordance with Islamic rules in Indonesia.